Comparison between Metschnikowia pulcherrima and Torulaspora delbrueckii used in sequential wine fermentations with Saccharomyces cerevisiae - Granchi, Lisa; Patrignani, Francesca; Bianco, Angela; Braschi, Giacomo; Budroni, Marilena; Canonico, Laura; Capece, Angela; Cauzzi, Anna; Ciani, Maurizio; Chinnici, Fabio; Civa, Valentina; Cocolin, Luca; et al. (Frontiers in Microbiology, 2025)
IntroductionThe interest toward the use of non-Saccharomyces yeasts in the winemaking process has been increasing because it has been demonstrated that they can contribute positively to the quality of wines; however, there is a gap in the literature on holistic approaches showing the effective contribution of non-Saccharomyces yeasts in sequential fermentations.Methods and resultsTwo commercial strains of Metschnikowia pulcherrima (Mp) and Torulaspora delbrueckii (Td) were used in sequential fermentations with Saccharomyces cerevisiae (Sc). The fermentations were monitored by evaluating cell viable counts, ethanol, glycerol, acids, amino acids, phenols, total antioxidant activity, total polysaccharides, and volatile organic compounds (VOCs). The results for amino acids pointed out after 2 days a lower utilization of amino acids by Sc per million of cells than Mp and Td; moreover, yeasts had a different preference hit. There were no significant differences in the final ethanol and glycerol content; however, the sequential fermentation Mp/Sc led to a significant decrease in malic acid levels, while the Td/Sc sequential fermentation resulted in a significantly lower acetic acid levels (13 mg/L vs 95–102 mg/L) and a higher phenol reduction. Finally, VOCs analysis showed differences in some compounds both after 2 days or at the end of fermentation (esters, and ketones, among others). Finally, both sequential fermentations resulted in a higher amount of polysaccharides.ConclusionThe findings of this research provide a basis for ensuring better management of sequential wine fermentation, and a possible approach for trials and data management.